2022
DOI: 10.3389/fbioe.2022.1081977
|View full text |Cite
|
Sign up to set email alerts
|

Robust intervention for oxidative stress-induced injury in periodontitis via controllably released nanoparticles that regulate the ROS-PINK1-Parkin pathway

Abstract: Graphical AbstractWe introduce novel mitophagy enhancer, MitoQ@PssL NPs exert excellently anti-inflammatory effects by activating mitophagy and clearing partial mitochondrial ROS, thereby accelarating osteogenesis in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The ligature-induced periodontitis mice model is a classical experimental model to mimic periodontitis in vivo. Although the exact mechanism of periodontitis pathogenesis is not fully elucidated, many studies have shown that it is linked to ROS-mediated oxidative stress [ 39 ]. Curcumin is a potent antioxidant that facilitates mitochondrial activities, reduces the level of ROS and lipid peroxidation, improves SOD activity and inhibits erastin-induced ferroptosis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ligature-induced periodontitis mice model is a classical experimental model to mimic periodontitis in vivo. Although the exact mechanism of periodontitis pathogenesis is not fully elucidated, many studies have shown that it is linked to ROS-mediated oxidative stress [ 39 ]. Curcumin is a potent antioxidant that facilitates mitochondrial activities, reduces the level of ROS and lipid peroxidation, improves SOD activity and inhibits erastin-induced ferroptosis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles that control the release of MitoQ [183] PDLSC sheets Promoted bone structures and collagen formation LC3 and p62 AuNPs [111] DFCs Increased biomineralization capability LC3A/B, ATG12, and AMPK Autophagy inhibitors [115] GMSCs Accelerated the osteogenic differentiation AMPK-Beclin 1 pathway Resveratrol [184] Note: Abbreviations: AMPK, adenosine monophosphate-activated protein kinase; ATG, autophagy-related proteins; AuNPs, gold nanoparticles; BIO, 6bromoindirubin-3′-oxime; BNIP3/NIX, BCL2 interacting protein 3/NIP3-like protein X signaling; CDs, carbon nanodots; CDots, carbon dots; DFCs, dental follicle cells; DFO, deferoxamine; FA-modified PCL nanofiber, fluorapatite-modified polycaprolactone nanofiber; FGF21, fibroblast growth factor 21; FUNDC1, FUN14 domain containing 1; GMSCs, gingival mesenchymal stem cells; LC3, microtubule-associated protein 1 light chain 3; mTOR-C1, the mechanistic target of rapamycin complex 1; NaF, sodium fluoride; PE, phosphatidylethanolamine; PI3KC3, the class III PI3K; PI3P, phosphatidylinositol-3-phosphate.…”
Section: Inhibited Osteoblastic Differentiation Lc3 Atg5 and P62mentioning
confidence: 99%
“… 45 Li X et al, on the other hand, noted that the reactive oxygen species (ROS) encapsulated in menaquinone (MitoQ; an autophagy enhancer) released the nanoparticle, released menaquinone effectively induced mitochondrial autophagy via the PINK1-Parkin pathway and successfully reduced oxidative stress by decreasing the number of reactive oxygen species, which was beneficial for periodontal regeneration. 67 The study of PDLSCs exosomes (PDLSCs-Exos) has also been gradually increasing. FOR THE FIRST TIME, Liu T et al revealed that miRNAs originating from PDLSCs-Exos might promote the osteogenic differentiation of BMSCs.…”
Section: Dental-derived Mesenchymal Stem Cellsmentioning
confidence: 99%